Blade research and demonstration platform. Issue 5 (September 2020) - Haselbach, Philipp U.; Zahle, Frederik; Berring, Peter; Semenov, Sergei; Voltá, Laura; Roqueta, I; Robert Verelst, David
Abstract: At DTU Wind Energy, a 12.6 m reference wind turbine rotor blade and the corresponding blade moulds were designed and manufactured. The entire blade design and the related test data will be published according to the FAIR principles. The blade moulds are intended to serve as a blade research and demonstration platform, allowing to realise theoretical concepts and testing these in full-scale on a wind turbine blade and thus enabling a comparison to numerical solutions. In this article, the preliminary blade design progress and process, initial load calculations and a 3D scan of the blade molds are presented.